A Part of and Apart from Sport: Practitioners’ Experiences Coaching in Segregated Youth Sport - Spencer-Cavaliere, Nancy (2017)
Sport can present a site of exclusion for many youth who experience disability even when it has a focus on inclusion (Fitzgerald, 2009). While sport practitioners can play a critical role in creating inclusive environments, they frequently struggle to do so. As a consequence, the sport opportunities for young people who experience disability are often inadequate and inequitable. The purpose of this study was to explore the experiences of youth sport practitioners who teach and coach youth in primarily segregated settings. The overall goal was to gain a better understanding of how sport practitioners think about disability and sport within the context of their practices. Guided by the method of interpretive description, we interviewed 15 sport practitioners. Analysis of the data led to the overarching theme, ‘a part of and apart from sport’, highlighting the ways in which segregated youth sport was understood to be more or less inclusive/exclusive by sport practitioners. Within this overarching theme, four subthemes were drawn: a) authentic connections, b) diversity and adaptations, c) expectations same…but different, and d) (dis)ability and competitive sport. While highlighting the need for self-reflective and knowledgeable coaches, our findings also bring attention to the concepts of ability and ableism and their impacts on the sport opportunities of youth who experience disability. Our discussion highlights the need to question assumptions underlying segregated sport.